Stability of partially encased columns under fire - Abdelkadir, Fellouh (2018)
The stability of partially encased columns under fire is evaluated, based on two different methods. The simple calculation method is presented and depends on new simple formulae, based on two major hypotheses, safer than the current method proposed in EN1994-1-2. This document establishes a designing method that considers the contours of temperature within the cross section after 30, 60, 90 and 120 minutes under fire exposure. The cross section is divided into four components in which the mechanical property of the material changes with the average temperature and part of the material is also neglected. An advanced calculation method, fully three-dimensional, is used to compare the results of the axial critical load. The results agree very well for fire ratings of 30 and 60 minutes.